Zastosowanie archimedesowskich funkcji powiązań (Archimedean copulas) o liczbie wymiarów większej niż 2 w analizie ryzyka portfela na rynku polskim - Rokita, Paweł (Modeling portfolio risk with multivariate Archimedean copulas - Polish Stock Market xxample, 2006)
This paper presents an extension of bivariate Archimedean-copula-based VaR model to suport analysis of portfolios with any number of components. Some empirical results for stock portfolios from the Warsaw Stock Exchange are presented in this article. VaR forecasts resulting from three Archimedean-copula models are analyzed and compared. The results are also compared with VaR forecasts obtained with classical multivariate normal model, used as a benchmark here.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (13); 2006; nr 1126, s. 280-288